NATIONAL FUND OF THE REPUBLIC OF KAZAKHSTAN AS A BASIS OF SUSTAINABLE DEVELOPMENT - Sartanova, N.T.; Tobylov, K.T. (PUBLISHINGS of Kostanay State Pedagogical University, 2018)
In this article considered general directions of development of the National Fund of the Republic of Kazakhstan, its role and the degree of influence on the formation of a new type of economy. The foreign practice of organizing sovereign funds or National Welfare Funds is given. Also, the article shows the mechanism of influence of the National Fund's resources on the economy in the conditions of the global financial crisis
Keywords: state budget; national welfare; sustainability; National Fund